Food and Nutrition Security under Different Farm Households in Bundelkhand (Indian Journal of Extension Education, 2022)
The concept food security was born out of an appreciation of the need to comprise nutrition in food security. Unlike food, which is generally described everything that community consume and drink to sustain existence and development, nutrition adds facet of wellbeing, a vigorous atmosphere, and nurturing practices. The study was conducted in Bundelkhand from 2018-19 to 2020-21. Respondents were selected based on proportional stratified random sampling technique. Data were collected by personal interviews using a structured interview schedule. The results revealed that among marginal farmers, the majority (70.37%) of respondents had low food security, followed by medium and high food security. Regression analysis was performed on the data to confirm the R2 value, and it was found that the independent variables included in the study were cumulatively responsible for explaining 63.80 per cent of the variability in the dependent variable.